Forensic investigation of clandestine laboratories - Christian, Donnell R. (Boca Raton : CRC Press, Taylor & Francis Group, 2022)
"Forensic Investigation of Clandestine Laboratories, Second Edition is fully updated to address all aspects of the forensic investigation of clandestine laboratories. While, the first edition focused on the domestic clandestine manufacture of contraband substances, this edition expands the scope to more fully address the clandestine manufacture of explosives that have become a threat that is global in nature. In clandestine laboratory operations, equipment is often simple, household chemical products are utilized, and the education of the operators basic. In fact, most of the time these elements individually are perfectly legal to sell and possess. However, the combination of all these elements is what becomes the scene of illicit activity and a criminal operation. In response to the increase in use of homemade explosive mixtures by terrorists, both domestically and internationally, the section clandestine manufacture of explosives is greatly enhanced. Topics are presented in a manner which, while detailed, will not compromise the tactics, techniques, or procedures utilized by law enforcement and military personnel in their ability to combat the clandestine manufacture of contraband substances and the battle against domestic and international terrorism. Key features: Examines tell-tale signs to look for in recognizing a clandestine lab Outlines how to safely process the site of a clandestine lab Details how to analyze collected evidence in the examination laboratory Provides guidelines as to what to derive from the physical evidence Offers specific tactics to effectively present the opinions associated with evidence that has been collected during the investigation in a written report, military style briefing or to a jury in a legal proceeding. Forensic Investigation of Clandestine Laboratories, Second Edition guides the reader through the process of recognizing these illegal manufacturing operations. Then it examines the methods as to how to compile the volume of associated evidence into a package that can be presented in a court of law, or to military commanders for decisive action. It is an invaluable resource, that will prove useful to chemistry lab technicians, forensic investigators, fire and first responder professionals, military personnel, police investigative agencies and narcotics units, and lawyer trying cases involving clandestine labs"--
Includes bibliographical references and index.
Keywords: Forensic sciences; Chemical laboratories